Systemic administration of epothylone-d recues memory and ameliorates Alzheimer’s disease-like pathology in APP/PS1 mice. - Fernández-Valenzuela, Juan José; Sánchez-Varo, Raquel María; De Castro Carratalá, Vanessa; Moyano, Francisco José; Vizuete, María Luisa; Dávila-Cansino, José Carlos; Vitorica Ferrández, Javier; Gutiérrez-Pérez, Antonia (My University, 2017)
Aims Cognitive and memory decline in Alzheimer's disease (AD) patients is highly related to synaptic dysfunction and neuronal loss. Tau hyperphosphorylation destabilizes microtubules leading to axonal transport failure, accumulation of autophagy/vesicular material and the generation of dystrophic neurites, thus contributing to axonal/synaptic dysfunction. In this study, we analyzed the effect of a microtubule-stabilizing drug in the progression of the disease in an APP751SL/PS1M146L transgenic model. Method APP/PS1 mice (3 month-old) were weekly treated with 2 mg/kg intraperitoneal injections of Epothilone-D (Epo-D) for 3 months. Vehicle-injected animals were used as controls. For memory performance, animals were tested on the object-recognition tasks, Y-maze and Morris water maze. Levels of Abeta, ubiquitin, AT8 and synaptic markers were analyzed by Western-blot. Hippocampal plaque burden, dystrophic and synaptic loadings were quantified after immunostaining by image analysis. Results Epo-D treated mice showed a significant improvement in the performance of hippocampus-associated cognitive tests compared to controls. This memory recovery correlated with a significant reduction in the AD-like hippocampal pathology. Abeta, APP and ubiquitin levels were significantly reduced in treated animals, and a decrease in both the plaque loading and the axonal pathology was also found. Finally, synaptic levels were significantly preserved in treated animals in comparison with controls. Conclusion Epo-D treatment promotes synaptic and cognitive improvement, reduces the accumulation of extracellular Abeta and the associated neuritic pathology in the hippocampus of APP/PS1 model. Therefore, microtubule stabilizing drugs could be considered therapeutical candidates to slow down AD progression.
Keywords: Alzheimer, Enfermedad de; Alzheimer; transgenic model; Therapy; Pathology